3D sand printing for automotive mass production applications. (2017) - Hackney, Philip M.; Wooldridge, Richard
Additive manufacturing (AM) of metallic products is seen by many to be commercially viable for only small and highly complex components, manufactured with difficult to machine materials using heat sintering process. In the automotive manufacturing sector, metal hard tooling is often required to produce mass produced components, and the tools are typically bespoke, large in size, inflexible and complex. Conventionally these tools have either been machined from solid billets or near-net-shape cast and then machined to achieve final size. Rapid casting technologies (RCT) use AM 3D sand printing process to manufacture sand mould tools used to create the production tooling. Adopters of this technology can achieve an increasingly agile and robust production process, RCT can also rewrite the design hand book for casting design. The research findings demonstrate that RCT can be successfully applied within the automotive industry, achieving considerable cost and time savings whilst improving quality and product flexibility.